2000
DOI: 10.1128/aac.44.3.802-805.2000
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro Activities of Ciprofloxacin, Gemifloxacin, Grepafloxacin, Moxifloxacin, Ofloxacin, Sparfloxacin, Trovafloxacin, and Other Antimicrobial Agents against Bloodstream Isolates of Gram-Positive Cocci

Abstract: The in vitro activity of gemifloxacin against 316 bloodstream isolates of staphylococci, pneumococci, and enterococci was compared with the activities of six fluoroquinolones and three other antimicrobial agents. Of the antimicrobial agents tested, gemifloxacin was the most potent against penicillin-intermediate and -resistant pneumococci, methicillin-susceptible and -resistant Staphylococcus epidermidis isolates, and coagulasenegative staphylococci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 7 publications
(1 reference statement)
4
19
0
1
Order By: Relevance
“…This result is comparable to those of previous studies, which have shown 8-to 32-fold greater activity for clinical isolates of methicillin-sensitive S. aureus (6,14,15,19,20,28,(30)(31)(32). The fact that in genetically defined mutants of S. aureus single mutations in either subunit of topoisomerase IV caused a twoto fourfold increase and a mutation in DNA gyrase caused a twofold increase in the MIC of gemifloxacin suggested similar targeting of the two enzymes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This result is comparable to those of previous studies, which have shown 8-to 32-fold greater activity for clinical isolates of methicillin-sensitive S. aureus (6,14,15,19,20,28,(30)(31)(32). The fact that in genetically defined mutants of S. aureus single mutations in either subunit of topoisomerase IV caused a twoto fourfold increase and a mutation in DNA gyrase caused a twofold increase in the MIC of gemifloxacin suggested similar targeting of the two enzymes.…”
Section: Discussionsupporting
confidence: 80%
“…It has been reported to have enhanced activity compared to that of older-generation fluoroquinolones against gram-positive aerobic bacteria (15,19,32) while retaining an activity similar to that of ciprofloxacin against gramnegative species (6,31). Similar to other quinolones, it is less potent against methicillin-resistant staphylococci (19), but recent work has shown that it might retain activity against some ciprofloxacin-resistant S. aureus strains (30,44).…”
mentioning
confidence: 99%
“…The compound has a broad spectrum of activity against Gram-positive and Gram-negative bacteria. [1][2][3] It is particularly active against Gram-positive organisms including penicillin-, macrolide-, and quinolone-resistant Streptococcus pneumoniae, 4 4-folds more potent than moxifloxacin against S. pneumoniae. 5 Gemifloxacin has also shown potent activity against other major pathogens involved in respiratory tract infections, including Haemophilus influenzae and Moraxella catarrhalis and the atypical organisms, Legionella pneumophila,Chlamydia spp., and Mycoplasma spp.…”
Section: Introductionmentioning
confidence: 99%
“…These species make up the heterogeneous group of CoNS that are less susceptible to antibacterials than S. epidermidis is. CoNS were in the past and are at present more resistant to the antibacterials studied than S. epidermidis is (73,(80)(81)(82)(83). This holds true for methicillin-susceptible and -resistant isolates, respectively.…”
Section: Pd Effects On the Human Resident Microflora As A Model Of A mentioning
confidence: 76%
“…To address these questions, publications were reviewed in which the MICs of all of the relevant antibacterial agents in different drug classes for S. aureus were compared to those for S. epidermidis (73)(74)(75)(76)(77)(78) and those for S. aureus were compared to those for CoNS (74)(75)(76)(77)(78)(79)(80)(81)(82)(83). Only those publications in which the activities of the agents against both species were compared directly with each other were selected.…”
Section: Pd Effects On the Human Resident Microflora As A Model Of A mentioning
confidence: 99%